2013
DOI: 10.1016/j.jcp.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale MDCT image-based breathing lung model with time-varying regional ventilation

Abstract: A novel algorithm is presented that links local structural variables (regional ventilation and deforming central airways) to global function (total lung volume) in the lung over three imaged lung volumes, to derive a breathing lung model for computational fluid dynamics simulation. The algorithm constitutes the core of an integrative, image-based computational framework for subject-specific simulation of the breathing lung. For the first time, the algorithm is applied to three multi-detector row computed tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 46 publications
1
85
0
Order By: Relevance
“…For example, when volumetric imaging of the bladder and urethra is conducted, dynamic volume images of the bladder and urethra are continuously captured by 640-slice MDCT during urination, and measurements of the bladder and urethra are made at the early, early to middle, middle, middle to late, and late phases by division of the images according to time point, and collected for statistical analysis. Previous studies have reported the use of DVCT for imaging of the osteo-odonto-keratoprosthesis lamina, acute chest pain or calcified coronary atherosclerotic plaque and airway deformation (17)(18)(19)(20). Therefore, in the present study, DVCT technology was applied to predict the bladder volume and urine flow rate of patients.…”
Section: Discussionmentioning
confidence: 98%
“…For example, when volumetric imaging of the bladder and urethra is conducted, dynamic volume images of the bladder and urethra are continuously captured by 640-slice MDCT during urination, and measurements of the bladder and urethra are made at the early, early to middle, middle, middle to late, and late phases by division of the images according to time point, and collected for statistical analysis. Previous studies have reported the use of DVCT for imaging of the osteo-odonto-keratoprosthesis lamina, acute chest pain or calcified coronary atherosclerotic plaque and airway deformation (17)(18)(19)(20). Therefore, in the present study, DVCT technology was applied to predict the bladder volume and urine flow rate of patients.…”
Section: Discussionmentioning
confidence: 98%
“…Cross‐sectional area of the trachea was calculated following methods previously described 7. Tracheal airflow was calculated using a validated method through computational fluid dynamics 8, 9.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, authors in [17] introduced a technique to build a multiscale breathing lung model from multidetector computer tomography (MDCT) volumetric data sets acquired at different inflation levels. Additional efforts towards modeling of airway structure (conducting airways), lung function (regional ventilation and boundary conditions), and flow characteristics (modeling of turbulent flow and its effect on particle transport) have been presented by [18].…”
Section: Introductionmentioning
confidence: 99%